Involvements of long noncoding RNAs in obesity‐associated inflammatory diseases. (20th October 2020) - Wijesinghe, Susanne N.; Nicholson, Thomas; Tsintzas, Kostas; Jones, Simon W.
Summary: Obesity is associated with chronic low‐grade inflammation that affects the phenotype of multiple tissues and therefore is implicated in the development and progression of several age‐related chronic inflammatory disorders. Importantly, a new family of noncoding RNAs, termed long noncoding RNAs (lncRNAs), have been identified as key regulators of inflammatory signalling pathways that can mediate both pretranscriptional and posttranscriptional gene regulation. Furthermore, several lncRNAs have been identified, which are differentially expressed in multiple tissue types in individuals who are obese or in preclinical models of obesity. In this review, we examine the evidence for the role of several of the most well‐studied lncRNAs in the regulation of inflammatory pathways associated with obesity. We highlight the evidence for their differential expression in the obese state and in age‐related conditions including insulin resistance, type 2 diabetes (T2D), sarcopenia, osteoarthritis and rheumatoid arthritis, where obesity plays a significant role. Determining the expression and functional role of lncRNAs in mediating obesity‐associated chronic inflammation will advance our understanding of the epigenetic regulatory pathways that underlie age‐related inflammatory diseases and may also ultimately identify new targets for therapeutic intervention.